Vocalizations modulate collective movement patterns in western gorillas - Lara Nellissen; Benjamin Robira; Terence Fuh; Klaus Zuberbühler; Shelly Masi (Behavioral Ecology and Sociobiology, 2026)
Group living can be advantageous but to benefit maximally individuals need mechanisms to maintain synchrony, which often requires signalling. We studied the role of vocal communication during a common coordination challenge in social animals: group travel. Western gorillas produce two call types during departures: grunts and grumbles. We investigated how these calls related to travel efficiency (linearity, speed, orientation accuracy) in three habituated groups of western gorillas ( Gorilla gorilla ) in the Central African Republic. We analysed 715 travel events towards distant resources. Gorillas called most during departure (grunts and grumbles) and upon arrival (grumbles only). Grumbles were produced mainly by high-ranking individuals or those waiting for others. For grumbles, but not grunts, higher calling rates at departure were linked to longer travel when groups were cohesive, but to shorter travel when they were not. Calling rates at departure did not influence orientation accuracy or linearity, which were generally high. During travel, increased calling generally reduced speed, except in cohesive groups where more grumbles were associated with faster travel. Travels with higher grumbles rates predicted travel towards unique or important food resources (e.g. clearings, fruiting trees). We concluded that gorillas use grumbles as “lead calls” to coordinate faster travel toward important food, whereas grunts function as general “cohesion calls”. Overall, these results show how great apes use vocal communication to coordinate long-distance group travel.

Corrigendum to “Born to be wild: Captive-born and wild Iberian lynx (Lynx pardinus) reveal space-use similarities when reintroduced for species conservation concerns” [Biol. Conserv. 294 (2024) 110646] - Pablo Cisneros-Araujo; German Garrote; Andrea Corradini; Mohammad S. Farhadinia; Benjamin Robira; Guillermo López; Leonardo Fernández; Marcos López-Parra; Maribel García-Tardío; Rafael Arenas-Rojas; Teresa del Rey; Javier Salcedo; et al. (Biological Conservation, 2024)

Born to be wild: Captive-born and wild Iberian lynx (Lynx pardinus) reveal space-use similarities when reintroduced for species conservation concerns - Pablo Cisneros-Araujo; German Garrote; Andrea Corradini; Mohammad S. Farhadinia; Benjamin Robira; Guillermo López; Leonardo Fernández; Marcos López-Parra; Maribel García-Tardío; Rafael Arenas-Rojas; Teresa del Rey; Javier Salcedo; et al. (Biological Conservation, 2024)

Context-dependent changes in maritime traffic activity during the first year of the COVID-19 pandemic - Alexandra Loveridge; Christopher D. Elvidge; David A. Kroodsma; Timothy D. White; Karen Evans; Akiko Kato; Yan Ropert-Coudert; Julia Sommerfeld; Akinori Takahashi; Robert Patchett; Benjamin Robira; Christian Rutz; et al. (Global Environmental Change, 2024)

How do primates decide where to feed? Insights from wild western gorillas - Benjamin Robira; Simon Benhamou; Erlich Obeki Bayanga; Thomas Breuer; Shelly Masi (Animal Behaviour, 2023)